2014
DOI: 10.1039/c4ra06715k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced reducibility and redox stability of Fe2O3in the presence of CeO2nanoparticles

Abstract: An oxygen-storage material with high reducibility and redox stability was obtained by anchoring isolated CeO2 nanoparticles on Fe2O3 rods after a high-temperature thermal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 33 publications
5
53
0
Order By: Relevance
“…16,21,22 Even though, α-Fe 2 O 3 is considered as one of the most promising pseudocapacitor electrode materials, the high-rate charge/discharge performance and cyclic stability are not fulfilled due to their poor electrical conductivity and metastability. 25 Based on the above consideration, we have attempted to exploit a new impressive visible light reactive hybrid CeO 2 /Fe 2 O 3 nanocomposite photocatalysts with a tailored bandgap for its potential application in photocatalyst and supercapacitors. 25 Based on the above consideration, we have attempted to exploit a new impressive visible light reactive hybrid CeO 2 /Fe 2 O 3 nanocomposite photocatalysts with a tailored bandgap for its potential application in photocatalyst and supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…16,21,22 Even though, α-Fe 2 O 3 is considered as one of the most promising pseudocapacitor electrode materials, the high-rate charge/discharge performance and cyclic stability are not fulfilled due to their poor electrical conductivity and metastability. 25 Based on the above consideration, we have attempted to exploit a new impressive visible light reactive hybrid CeO 2 /Fe 2 O 3 nanocomposite photocatalysts with a tailored bandgap for its potential application in photocatalyst and supercapacitors. 25 Based on the above consideration, we have attempted to exploit a new impressive visible light reactive hybrid CeO 2 /Fe 2 O 3 nanocomposite photocatalysts with a tailored bandgap for its potential application in photocatalyst and supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…There are two reduction peaks of Fe 2 O 3 . The first peak is ascribed to the reduction of Fe 2 O 3 into magnetite Fe 3 O 4 , and the second peak around 720 °C with a higher H 2 uptake is associated with the subsequent multiple reduction of magnetite Fe 3 O 4 to Fe through FeO as an intermediate . With the addition of the second metal oxide, the reduction peaks of the mixed metal oxides show different behaviours.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers also reported that Fe 2 O 3 , together with CeO 2 , forms a perovskite-type CeFeO 3 , which improved the reversibility of the Fe 2 O 3 redox reaction. 40,[45][46][47] Gu et al 40 reported that the abundant Ce 3+ ions in CeFeO 3 might act as a catalyst to enhance the reducibility of the Ce and Fe oxides. Zhu et al 47 found that the formation of CeFeO 3 enhanced the oxygen mobility of the CeO 2 -Fe 2 O 3 OC.…”
Section: Cyclic Testsmentioning
confidence: 99%